Strengthening of duplex stainless steel processed by equal channel angular pressing (ECAP) - Muñoz Bolaños, Jairo Alberto (2022)
This manuscript presents the study of the microstructural evolution, plastic anisotropy, and mechanical behavior of a duplex stainless steel (DSS) processed by the equal channel angular pressing (ECAP) technique. The ECAP process produced shear bands affecting both phases, austenite and ferrite, which in turns act as preferential sites for the appearance of the new ultrafine grains. Microstructural observations indicated grain sizes smaller than 300 nm in both phases. However, marked differences in the grain boundary misorientations were observed. Most ferrite grain boundaries showed low misorientations (average misorientation of 30°). In contrast, the austenite grain boundaries were mainly dominated by high-angle grain boundaries (average misorientation of 39°). The ECAP processing allowed to reach a yield strength over 1.1 GPa after one ECAP pass. Dislocations formed walls in the ferrite, while they were distributed evenly in the austenite grains creating plastic gradients between the two phases. Through the visco-plastic self-consistent model, it was found that austenite and ferrite strain hardening at different rates, generating plastic instabilities at different strain magnitudes. In this way, it was shown that austenite is the phase that provides more hardening while ferrite provides ductility. Regarding the anisotropy of the steel, crystal plasticity simulations showed that during the first passes of ECAP, the Lankford coefficients increase notably due to the heterogeneous microstructure of sheared grains with a higher density of defects forming subgrains in ferrite than austenite. Moreover, the austenite was more responsible for the larger planar anisotropy (Δ r = 2.18) values than ferrite (Δ r = 1.67) after two ECAP passes.